TINGKAT KEPUASAN PENGUNJUNG TERHADAP OBJEK WISATA MAKATETE HILLS DESA WAREMBUNGAN KECAMATAN PINELENG KABUPATEN MINAHASA (Visitor Satisfaction Level to Tourism Attraction Makatete Hills Warembungan Village Pineleng Sub District Minahasa Regency) - Gledies Feiby Hihola; Caroline B. D. Pakasi; Oktavianus Porajouw (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2020)
The objective of this study is to measure the level of visitor satisfaction with the attractions of Makatete Hills, Warembungan Village, Pineleng Sub District, Minahasa Regency. This research was conducted for 3 months, from August 2019 to October 2019, the data used in this study were primary and secondary data primary data obtained by distributing questionnaires to visitors to Makatete Hills and secondary data obtained from literature studies in the form of literature, book articles and journals.The research results of this study showed that the Level of Visitor Satisfaction of Makatete Hills Tourism Objects in Warembungan Village, Pineleng Subdistrict, Minahasa Regency, can be concluded to be at the level of 79.33 with the criteria of Satisfaction, even though it is within the satisfied criteria, the manager must pay more attention to the access road to the Makatete Hills location.Keywords: Level of Visitor Satisfaction, Tourist attraction